Lambl’s filaments as a cause for cardiogenic embolism of cerebral vessels and coronary arteries - Bogdan, T.V.; Lizogub, V.G.; Savchenko, O.V.; Bogdan, V.V.; Vinokurova, А.S.; Orzheskovsky, V.V. (Доповіді НАН України, 2021)
The article presents a specific clinical case and literature data on a rare finding in the heart cavity — Lambl’s filaments. Histologically, these are cells of fibroelastic tissue covered with stroma and epithelial layer. They do not have a vascular sheath, so they are devoid of granulation tissue. Lambl’s growths occur on both their own and prosthetic heart valves. Very rarely, threads can also be seen in areas other than heart valves such as the papillae, atria, and chords. These lesions can be seen on the echocardiogram accidentally or in connection with serious complications such as embolic stroke or acute coronary syndrome after their separation and distribution to distant organs. Lambl’s growths occur in adults and children, but the prevalence is higher in the former and increases with age. On the echocardiogram, the incidence reaches a peak between the ages of 61 and 70, and then decreases due to the aging of heart valves, which are increasingly calcified. The disease is more common in men than in women.